2001
DOI: 10.1080/18811248.2001.9715105
|View full text |Cite
|
Sign up to set email alerts
|

Carbon and Oxygen Isotope Separation by Plasma Chemical Reactions in Carbon Monoxide Glow Discharge

Abstract: The separation of carbon and oxygen isotopes in CO glow discharge has been studied. The isotope enrichment in the products was measured by quadru-pole mass spectrometer. The reaction yield and empirical formula of solid phase products were determined by the gas-volumetric analysis. The stable products obtained in our experiment are CO 2 and solid polymers formed on the discharge wall. The polymer consists of both carbon and oxygen and the oxygen/carbon mole ratio in the polymer is 0.35±0.05. The isotope enrich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 16 publications
2
17
1
Order By: Relevance
“…10). Although high 13 C enrichment coefficients have been obtained for stable products in our experiment with respect to the present commercial carbon isotope separation method, 3,[5][6][7] our experimental enrichment coefficients are smaller than those of theoretical predictions 11,12) and experimental results for intermedi-ates: vibrationally excited CO molecules 13) and fragmentation specie C + in the mass spectrometer, which would be the cracking pattern of gaseous C 3 O 2 .…”
Section: Introductioncontrasting
confidence: 43%
See 2 more Smart Citations
“…10). Although high 13 C enrichment coefficients have been obtained for stable products in our experiment with respect to the present commercial carbon isotope separation method, 3,[5][6][7] our experimental enrichment coefficients are smaller than those of theoretical predictions 11,12) and experimental results for intermedi-ates: vibrationally excited CO molecules 13) and fragmentation specie C + in the mass spectrometer, which would be the cracking pattern of gaseous C 3 O 2 .…”
Section: Introductioncontrasting
confidence: 43%
“…7) To analyze isotope enrichment process and enrichment dilution mechanism, we perform numerical simulation of kinetic processes in the present study. The kinetic model is developed to reproduce experimental results and to estimate optimum discharge condition and isotope separation potential of this method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In both systems, a lowtemperature CO/Ar/O 2 plasma was used. In general, the advantages of low-temperature plasma CVD using CO instead of hydrocarbons as the carbon source gas are as follows: (1) the deposition of amorphous carbon is suppressed even at low temperatures (Muranaka et al, 1991;Stiegler et al, 1996); (2) the CO disproportionation reaction, CO+CO → CO 2 +C, is thermodynamically favorable at low temperatures; (3) vibrationally excited molecules are formed which enhance reactions at low temperature, such as CO(v)+CO(w) → CO 2 +C (Plonjes et al, 2002;Capitelli 1986;Mori et al, 2001); (4) C 2 molecules are known to be formed effectively through the reactions C + CO + M → C 2 O + M and C + C 2 O → C 2 + CO and can be precursors for the deposition of functional carbon materials (Caubet & Dorthe, 1994;Ionikh et al, 1994;McCauley et al, 1998). Figure 2(a) shows a schematic diagram of the experimental apparatus for the DC-PECVD system.…”
Section: Synthesismentioning
confidence: 99%
“…To our knowledge, few attempts at low-temperature plasma-enhanced chemical vapor deposition (PECVD) of CNFs/CNTs using CO as the carbon source have been made (Han et al, 2002;Plönjes et al, 2002). In general, the advantages of low-temperature plasma CVD using CO instead of hydrocarbons as the carbon source gas are as follows: (1) the deposition of amorphous carbon is suppressed even at low temperatures (Muranaka et al, 1991;Stiegler et al, 1996); (2) the CO disproportionation reaction CO + CO → CO 2 + C is thermodynamically favorable at low temperature; (3) vibrationally excited molecules are formed and enhance reactions at low temperature, such as CO(v) + CO(v) → CO 2 + C (Capitelli et al, 1986;Mori et al, 2001;Plönjes et al, 2002). In the previous study, we have reported that the vertically aligned CNFs were able to be synthesized at temperature as low as 90 • C using low temperature CO/Ar/O 2 plasma system (Mori et al, 2007;Mori and Suzuki, 2008).…”
Section: Introductionmentioning
confidence: 99%